Romantic relationship : the issues faced in a conflict among young adults - J.Lavanya Jayakobi,; Sam, Jeng Mun (Penerbit Universiti Kebangsaan Malaysia, 2021)
The phenomenon of conflict in a romantic relationship is a unique experience which differs from one to another individual. By using the interpretative phenomenological analysis (IPA), the current research aims to answer the question “Does the Gottman’s Four Horsemen of Apocalypse applies in romantic relationship among young adults? through the interviews of 16 participant age range from 18 to 25 years old. From the data collected, three superordinate themes were found which are communication styles, individual reactions and problems solving, as well as subthemes. The findings show everyone’s experiences on conflict in romantic relationship is extremely personal, and the carrying traits on solving the conflict in their romantic relationship. The information provides valuable insight on the experiences of conflict in romantic relationship among young adults to counsellors and therapists, better equipping them to service university students.